2018
DOI: 10.18320/jimd/201805.0111
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Loneliness and Suicidal Ideation in Private Medical and Dental Students in Jeddah, Saudi Arabia

Abstract: Introduction: The aim of this study was to assess the prevalence of suicidal ideation, suicidal attempts, and loneliness among dental and medical students in the western region of Saudi Arabia. Materials and Methods: This cross-sectional study investigated 607 dental and medical students and interns in private colleges in Saudi Arabia. A self-administrated questionnaire was based on the Revised UCLA Loneliness Scale. Suicidal ideation and attempts were measured by a questionnaire adopted from previous research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
79
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(95 citation statements)
references
References 17 publications
11
79
3
2
Order By: Relevance
“…The study of resilience and its significance to gender and how it may or may not influence resilience has been encouraged . Higher overall scores, structured style, social resources resilience, and lower perception of self‐resilience among women (as compared to males) were found, aligning with many previous study results .…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The study of resilience and its significance to gender and how it may or may not influence resilience has been encouraged . Higher overall scores, structured style, social resources resilience, and lower perception of self‐resilience among women (as compared to males) were found, aligning with many previous study results .…”
Section: Discussionsupporting
confidence: 79%
“…An Australian study found that certain personality profiles aligned with psychological maturity serving as a strong predictor of one's ability to cope with life's challenges, accept limitations and develop strategies to bounce back from adversity . An examination of the relationship between resilience, happiness, and life satisfaction in Saudi Arabian dental students found resilience to be significantly correlated to both life satisfaction and happiness . This study also found a higher level of resilience in females and those persons from families of higher income .…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…When students' life satisfaction levels are examined, it is seen that they are satis ed with their lives. When the studies in the literature were examined, life satisfaction levels were found to be high in the studies conducted with the students of medicine and dentistry in Saudi Arabia by Aboalshamat et al [25], with medical students in China by Wang et al [26], with nursing students in Korea by Kim [27]. As individuals with high life satisfaction have a psychologically, socially and physically healthy life, high level of social functionality, more positive relationships in their social environments, a cognitive structure and productivity that are open to personal development, compatible with their lives [28], it is thought that the high level of life satisfaction of individuals in the health sector will have a positive impact on health services.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, almost all Khateebs supported that the main reasons underlying suicide include both the fragile religious faith and mental illnesses, and other studies [70][71][72] partially supported these findings. One tenth of RMLs expressed that suicide and suicidal attempts never occurred in Saudi society that is not tenable [73][74][75]. Religious mosque leaders need training workshops that target suicide, suicidal ideation and suicidal attempts and nondeliberate self-injurious behaviors, and presently Khateebs are taking MH training organized by NCPMH.…”
Section: Discussionmentioning
confidence: 99%